Microbiological quality of the air in the area of influence of the former wastewater treatment plant in Cajamarca, Peru - Rodriguez-Zevallos, Claudia E.; Sanchez-Altamirano, Jessica K.; Sanchez-Peña, Marco A.; Diaz, Kenny (Frontiers in Environmental Science, 2025)
It has been determined that there is air pollution within wastewater treatment plants and their surrounding areas. This impacts the health of nearby populations. Therefore, this research aimed to evaluate the air’s microbiological quality in the area of influence of the former Wastewater Treatment Plant (WWTP) in the city of Cajamarca. Microbiological air sampling was conducted during the rainy and dry seasons using the RCS Standard Hycon air sampler, planting on tryptic soy agar medium to determine the total count of all microorganisms, bacteria, and fungi separately. OSHA (Occupational Safety and Health Administration), PN-89/Z-04111/02, and PN-89/Z-04111/03 were the standards used to determine the air quality of the study area since Peru currently does not have such regulation standards. The highest values obtained were 4560 CFU/m³ and 4360 CFU/m³ during the dry season. Sixteen concentrations of the total microorganism count exceeded the limits established by OSHA standards, and ten concentrations of bacteria exceeded the Polish standard PN-89/Z-04111/02. Although the concentrations of fungi were high, they did not exceed any reference limits. We determined a positive correlation between the concentration of microorganisms and the relative humidity, with a maximum of 85.67% humidity during the dry season. Additionally, a negative correlation with wind speed was found, with values ranging from 0.37 m/s to 2.58 m/s during the dry season and from 0.37 m/s to 1.87 m/s during the rainy season. Genera of public health importance such as Staphylococcus and Penicillium were identified. Finally, a survey was conducted among the nearby population to assess the impact on public health. And, it was established that the health impact on the surrounding populations is mainly low.